Richard Wagner’s place in the history of ideas during the last third of the 19th century - Popov, Ivan (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2025)
The paper examines certain key points of the composer Richard Wagner’s aesthetic doctrine, reconstructing both their origins and their influence on the philosophical and artistic work of Friedrich Nietzsche and Thomas Mann. The particular conferment of political functions to art that we find in Wagner is the result of a diagnosis of Western European culture, according to which modern society has developed in an all too one-sided way, suppressing any creative impulses in the individual. The text traces how Nietzsche and Mann take up and further develop these ideas. The historical-anthropological approach to the past of culture is also able to illustrate important differences that exist between the German and Bulgarian reception of said ideas during the last decades of the nineteenth century.
Keywords: Richard Wagner; Friedrich Nietzsche; Thomas Mann; art and politics; modern society